A Content Analysis of the Websites of the World's Top 50 Universities in Medicine. Issue 3 (3rd July 2021) - Rafiq, Sadaf; Ashiq, Murtaza; Ur Rehman, Shafiq; Yousaf, Furkan
ABSTRACT: This study examined the quality of library websites of QS world top-ranked medical libraries' services, resources, information dissemination tools, and training opportunities to library users. Moreover, this study also explores the medical resources provided by medical universities remotely. The study used web content analysis method. A checklist consisting on nine main categories and 87 indicators have been finalized. The website quality assessment score indicated that none of the university libraries in the discipline of "medicine" gained 100% score. However, two university libraries (University of Cambridge and University of Washington) scored more than 90%. The finding revealed that "patron-driven acquisition" was a least common service (n = 6) and significant number of university libraries (42%) were still not using mobile apps. The most famous five dissemination tools are Facebook, Twitter, Instagram, YouTube, and LinkedIn. While web of science, PubMed, PsycINFO are significantly available databases to most of the libraries. This is an in-depth and first study investigating the web content analysis of world top-ranked medical universities libraries.